SAMARA FM TULUNGAGUNG RADIO MARKETING COMMUNICATION STRATEGY IN ATTRACTING ADVERTISERS - Yunita Indinabila; Maegi Muhammad Rizqi; Mukhamad Ainul Yaqin (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2021)
Abstract Radio is a mass media that has existed for a long time and survived until now. Although many other information and entertainment media appear along with the times, radio still has its fans. To find out the marketing communication strategy implemented by Radio Samara FM Tulungagung in increasing the interest of advertisers. To find out the obstacles faced by Radio Samara FM Tulungagung in implementing marketing communication strategies to increase the interest of installers. To find out the solution from the head of Radio Samara FM Tulungagung in implementing a marketing communication strategy. This research uses a qualitative research approach. Based on the level of explanation, this research is called descriptive research. The data in this study consists of two types, namely primary data and secondary data. In this study, the primary data source was an employee of Samara FM Tulungagung Radio.